Analisis Kreativitas Siswa pada Praktik Menggambar Dekoratif dalam Mapel SBDP Kelas III - Tarisa Meylda Salsabilla; Singgih Adi Prasetya; Ruku Mandar Sary (Pascasarjana IAI Nasional Laa Roiba Bogor, 2025)
The background that prompted this research was based on observations during a preliminary study at one of the State Elementary Schools in Pucakwangi District, Pati Regency, Central Java.. In the drawings produced by students, each student draws with different creativity according to their own imagination. For example, when students are asked to do decorative drawings with free themes, students will draw with different themes, some will draw flowers, butterflies, trains and many more. The coloring and decoration motifs on objects also vary. In this case, the author is interested in knowing the decorative drawing creativity of class III. Based on the data analysis results, it can be concluded that the learning process was conducted in the Grade III classroom.This research used a qualitative descriptive approach. The learning activities were attended by 17 students. The learning process consisted of opening activities, core activities, and closing activities. During the learning process, the teacher explained the material on decorative drawing. Based on the drawing works, students were able to draw using their own ideas. All the drawings made by the students were already aligned with their original form. The students were able to creatively incorporate decorative elements into their drawings. The drawings contained decorative elements consisting of dots, lines, shapes, textures, and colors. The coloring of the drawings was good, and the students were able to combine colors effectively. It was concluded that 4 students produced drawings categorized as very creative, 9 students produced drawings categorized as creative, and 4 students were categorized as moderately creative. Based on the research results, the suggestion is to further enhance the students' creativity in drawing, particularly for those with lower levels of creativity.